2011
DOI: 10.1038/nclimate1059
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of climate change and willingness to save energy related to flood experience

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. One of the reasons that people may not take action to mitigate climate change is that they lack first-hand experience of its potential consequences. From this perspective, individuals wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
532
11
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 823 publications
(629 citation statements)
references
References 20 publications
33
532
11
17
Order By: Relevance
“…These findings give cause for hope at a critical time, contrasting with the pessimistic implications of research suggesting people's motivation to act on climate change are limited by ideology [1][2][3] , or relies on widespread personal experience of climate change 28,29 (when it may be too late to mitigate). Communicating about co-benefits of addressing climate change can provide another way to engage and motivate the public to act, and to support government action, that do not depend on being convinced or concerned about climate change.…”
contrasting
confidence: 40%
“…These findings give cause for hope at a critical time, contrasting with the pessimistic implications of research suggesting people's motivation to act on climate change are limited by ideology [1][2][3] , or relies on widespread personal experience of climate change 28,29 (when it may be too late to mitigate). Communicating about co-benefits of addressing climate change can provide another way to engage and motivate the public to act, and to support government action, that do not depend on being convinced or concerned about climate change.…”
contrasting
confidence: 40%
“…Involvement of local populations in designing and implementing these interventions could reduce effects of hydro-climatic changes and improve adaptive capacity of the region (Sissoko et al 2010). Higher adaptation of residents' downstream Kainji dam was due to flooding witnessed as a result of spill discharge from the reservoir and shows that people that experiences frequent flooding express more concern and greater willingness to take action against climate change (Spence et al 2011). Respondents embraced the use of local level water treatment as a result of inadequate drinking water supplies which keep the communities on high alert of water borne disease like cholera that is rampant in the region (Okeke et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have explored the incongruence between environmental knowledge/attitudes and behaviours (Kollmuss and Agyeman 2002), or between climate change awareness and engagement with mitigation (Spence et al 2011). In two Australian studies, Waitt et al (2012) found that low-income households engaged in sustainable practices despite not identifying as 'green'; and Klocker et al (2012) found that older family members in multi-generational households (some of whom were climate change sceptics) valued frugality.…”
Section: Implication 2: Knowledge May Not Be Necessary For Householdmentioning
confidence: 99%